Analysis of mobile robot path planning with artificial potential fields - Hamzah, Ahmad; Ahmad Nuur Fakrullah, Mohamad Pajeri; Nur Aqilah, Othman; Mohd Mawardi, Saari; Mohd Syakirin, Ramli (Springer Singapore, 2019)
This paper presents an analysis of a mobile robot path planning using potential field technique. The mobile robot has four wheels which can all be driven and steered independently. For simplicity, this paper assumes Ackermann steering such that the vehicle can be approximated as a two-wheel system (commonly known as a bicycle model) for path planning purposes. The potential field method that emphasizes on attractive potential field and repulsive potential field are proposed for analysis in this paper for path planning. The control gains which represents the attractive and repulsive force are studied to determine the effectiveness of the proposed method. Based on the simulation results, the robot able to avoid obstacle and at the same time arrived at the goal. The robot priorily do not pose any information on the environment and then moves until it reach its goal. Different cases of the potential fields and landmarks positions are also presented to determine the robot performance.